The fortune cookie [videorecording (DVD)] - Wilder, Billy, 1906-2002; Wilder, Billy, 1906-2002; Wilder, Billy, 1906-2002; Lemmon, Jack; Matthau, Walter; Rich, Ron, 1938-; West, Judy (Actress) (MGM/UA vintage classics., 2001)
A TV cameraman, trampled by a half-back while shooting a football game, and his shyster brother-in-law team up to defraud an insurance company in a million dollar law suit.